2011
DOI: 10.1097/htr.0b013e318218dd22
|View full text |Cite
|
Sign up to set email alerts
|

Impairments in Learning, Memory, and Metamemory Following Childhood Head Injury

Abstract: Traumatic brain injury severity affected prospective judgments of memory performance and learning strategies, but did not appear to affect either word retention or the forgetting of words over a delay. Implications for rehabilitation are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 45 publications
4
9
0
Order By: Relevance
“…This is in agreement with some prior studies, 6,7,28 but not all. 29 It is important to note that improvement over time in children with TBI has been noted on psychometric measures, 30,31 but that this performance on standardized assessments in controlled settings does not necessarily translate into functional improvements in daily settings. Clinicians and researchers should focus more on functional daily skills, participation in activities, and quality of life such as that measured in this study, as these factors have significantly greater bearing on long-term outcome and functioning in adulthood than individual test performance.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with some prior studies, 6,7,28 but not all. 29 It is important to note that improvement over time in children with TBI has been noted on psychometric measures, 30,31 but that this performance on standardized assessments in controlled settings does not necessarily translate into functional improvements in daily settings. Clinicians and researchers should focus more on functional daily skills, participation in activities, and quality of life such as that measured in this study, as these factors have significantly greater bearing on long-term outcome and functioning in adulthood than individual test performance.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to elucidate recovery of memory and metamemory function following childhood TBI, Crowther et al (2011) classified children with TBI into mild, moderate, and severe groups and considered memory and metamemory performance in a multi-trial verbal learning task across five assessments over a 2 year period. The results indicated that children with moderate and severe TBI showed the greatest improvement across all measures over time, but the performance gap between them and the mild TBI group increased.…”
Section: Neurodevelopmental Disordersmentioning
confidence: 99%
“…Prediction was difficult for both healthy children and children with TBI, self-estimation was significantly less correlated with actual performance in braininjured children than in typically developing ones [35], and children with brain injury overestimated their memory performance [31]. Similarly, in Hanten et al [32,33] and Crowther et al [34] studies, children who had sustained a TBI had poor estimation of their memory span and overconfidence in performance when compared to healthy children and children with mild TBI [32], suggesting impaired metacognition. The scarce literature assessing awareness in children with brain injury explores metacognitive skills such as prediction and evaluation, using assessments performed in structured, un-ecological environments.…”
Section: Introductionmentioning
confidence: 85%
“…However, to date, objective measurement of awareness in children with TBI is scarce (see Wales et al [29] for a review) and most studies evaluate single metacognitive skills such as prediction, evaluation and confidence of performance [30][31][32][33][34]. Conversely, Beardmore et al reported the use of the ''Knowledge Interview for Children'' (KIC) [9], a semi-structured interview related to 12 areas of knowledge about TBI (coma, story of the accident, brain functioning,.…”
Section: Introductionmentioning
confidence: 99%